Sticky information vs. sticky prices: A horse race in a DSGE framework - Mathias Trabandt (Sveriges Riksbank, 2007)
How can we explain the observed behavior of aggregate inflation in response to e.g. monetary policy changes? Mankiw and Reis (2002) have proposed sticky information as an alternative to Calvo sticky prices in order to model the conventional view that i) inflation reacts with delay and gradually to a monetary policy shock, ii) announced and credible disinflations are contractionary and iii) inflation accelerates with vigorous economic activity. I use a fully-fledged DSGE model with sticky information and compare it to Calvo sticky prices, allowing also for dynamic inflation indexation as in Christiano, Eichenbaum, and Evans (2005). I find that sticky information and sticky prices with dynamic inflation indexation do equally well in my DSGE model in delivering the conventional view.
Keywords: E0; E3; 330; sticky information; sticky prices; inflation indexation; DSGE; Inflationsbekämpfung; Preis; Anpassung; Informationsverbreitung; Preisrigidität; Dynamisches Gleichgewicht; Stochastischer Prozess; Theorie